Acoustic comfort in a worship space made of cross-laminated timber. Issue 2 (June 2019) - Fratoni, Giulia; D'Orazio, Dario; Barbaresi, Luca
The construction of a new worship space in cross-laminated timber provides a good opportunity to include acoustic needs in the whole design development. The surface porosity and the lightweight of wooden elements may be carefully considered in order to improve the intelligibility of priests' voice. In this work, a practical approach for obtaining a global acoustic comfort using sustainable materials is provided, using geometrical acoustic simulations. Material properties and architectural geometries were taken into account in order to evaluate subjective reverberation, speech intelligibility, and spatial perception over the whole audience. Results show how the sound energy distribution in the case study follows the sound field models proposed by scholars and how the ceiling shape—inspired by industrial sheds—contributes to the acoustic comfort of the faithfuls.